Room-temperature ferromagnetic wide bandgap semiconducting fluorinated Graphene-hBN vertical heterostructures. (November 2021) - Sahoo, Krishna Rani; Sharma, Rahul; Bawari, Sumit; Vivek, S.; Rastogi, Pankaj Kumar; Nair, Swapna S.; Grage, Stephan L.; Narayanan, Tharangattu N.
Abstract: Low Z element based room temperature ferromagnetic materials are highly sought after for many applications. In this work, we report the development of fluorine functionalized graphene-hBN out-of-plane heterostructures (hBNCF), which possess large room temperature ferromagnetic ordering (magnetization ∼ 0.05 emu/g and coercivity ∼ 420 Oe) and exhibit T2 relaxation enhancement (0.55 s −1 found for D2 O was increased to ∼7 s −1  at 1 mg/ml) in water without causing the T1 . The ferromagnetic nature of the hBNCF powder devoid of any metallic magnetic impurities was further shown by magnetic force microscopy. Layered structures of hBNCF that have an optical bandgap of ∼3.89 eV were produced using a two step method: Shear exfoliated hBN layers were modified by surface graphitisation to result into layered graphene heterostructures (hBNC), which were then functionalized with fluorine. Apparent ferromagnetic properties arise from these large scale, vertical, non-van der Waals connected, crystalline layer structures. Density functional calculations show the role of out-of-plane covalently connected BN domains and their interaction with fluorine, that causes the formation of new states in the graphitic lattice. These states exhibit a spin splitting, which contributes to the observed large magnetic ordering. Graphical abstract: Image 1 Highlights: Using fluorination, we produced hBNCF) with RT ferromagnetism, a magnetization of ∼0.05 emu/g and a coercivity of ∼420 Oe. The unusual magnetism is due to spin-split states caused by out-of-plane covalently linked BN domains and adjacent C-F bonds. hBNCF exhibits T2 NMR relaxation enhancement indicating its ferromagnetic nature and potential as MRI contrast agent.